Posegi v zasebnost s sodobno informacijsko tehnologijo v davčnem postopku - Zgaga Markelj, Sabina (Pravni letopis, 2025)
Some powers typically associated with the police in criminal proceedings are also exercised by authorities in non-criminal proceedings (e.g., the Financial Administration of the Republic of Slovenia - FURS). Although the statutory and regulatory frameworks are similar, relevant case law - particularly of the Constitutional Court, the European Court of Human Rights, and the Court of Justice of the European Union - has largely developed around police powers. Increasingly, these courts also address the powers of other state authorities that interfere with privacy protected by the Constitution, international treaties, and EU law. Given the distinct legal frameworks governing those powers, various constitutional questions arise, including the admissibility of evidence in criminal proceedings. This article critically examines several Constitutional Court decisions on FURS’s privacy-intrusive uses through the use of modern information technology: Decision U-I-33/23 of 16 May 2024 concerning the use of GPS tracking for financial-investigation purposes; and Decision U-I-11/20, Up85/20 of 3 October 2024 on whether online space can be equated with physical space. The article concludes by assessing the admissibility of transferring evidence from non-criminal to criminal proceedings.
Keywords: davčni postopek; EU law; informacijska zasebnost; information privacy; komunikacijska zasebnost; pravo Evropske unije; privacy of communications; reasonable expectation of privacy; tax procedure; utemeljeno pričakovanje zasebnosti